Christianity and the history of the church „The Nativity of the Blessed Virgin” of Balti-Slobozia (Confluenţe Bibliologice, 2014)
The study of documents and material published show that most saint houses of the Balti County occurred in the second half of the 18th Century, being built of wood in villages with old traditions. In Balti city Saint Houses have started to build similar neighbouring village-made of wood, and later of stone. It talks about the history of the church in Slobozia-Balti (1888), which ﬁrst was built from wood, possible built until 1742, the year shown on stone cut, found during excavations in the yard of the church, with the nomination of authors.
Keywords: history of Bessarabia; Bessarabian church